Simultaneous presence of ferroelectricity and magnetism in Mo-doped CoFe2O4 - Dwivedi G.D.; Tseng K.F.; Chan C.L.; Shahi P.; Chatterjee B.; Ghosh A.K.; Yang H.D.; Chatterjee S. (My University, 2025)
Signature of ferroelectricity has been observed for the first time in magnetically ordered Co(Fe1-xMox)2O 4. The structural property of Co(Fe1-xMox) 2O4 (x ranges from 0 to 0.1) indicates that Mo goes into the tetrahedral site. The frequency dependent P-E loop indicates the existence of weak ferroelectricity in Mo-doped CoFe2O4. © 2010 American Institute of Physics.